Pengembangan Gim Kuis Pengenalan Sejarah Perang Dunia I Berbasis Desktop - Zanuar Fitrian Ardi; Harya Bima Dirgantara (UNIVERSITAS KALBIS, 2022)
The purpose of this research is to create an educational quiz game about the introduction of history of World War I desktop-based and can be run on a desktop with a Windows 10 operating system. This game was built using a 2D unity game engine. the method used to make this educational game using the Game Development Life Cycle (GDLC) method. This method consists of 6 stages: Initiation, Pre-Production, Production, Testing, Beta, and Release. In the final results of the educational game about introduction of World War I history with the title